7 - Globalisation and Technology: Problems and Prospects for the Agricultural Sector in Africa: DOI: 10.4314/ad.v30i4.22244 - Agbu, Osita (Africa Development, 2005)
This paper examines the linkage between globalisation as a phenomenon and technology as the catalyst on the state of the agricultural sector in Africa. It is observed that though agriculture is the dominant economic sector in Africa, it is currently facing a food crisis of monumental dimensions. Figures pertaining to food production growth rates and the percentage share of agriculture in total labour force are presented to highlight the poor state of this sector. Apart from the impact of globalization on the sector, the paper sought to determine the link between technological capacity and the food crisis in Africa on the one hand, and the prospects for increased technological inputs in African agriculture on the other. Fundamentally, the paper argues that Africa cannot begin to benefit from global developments in trade, technology and therefore improving the welfare of its peoples until food security is reasonably attained. It recommends the use of science-based technology generation to ensure sustainable agricultural development. African governments are called upon to balance the vicissi tudes of the multilateral framework on agriculture with their immediate national objectives. Finally, the author opines that a brighter future awaits those coun tries that can competently manage the impact of globalization on this sector, while infusing appropriate technologies to ensure food security.